The aesthetics of Malay material culture (KUKURAN): a study of form, content and style / Zulkfli Md Yusoff - Md Yusoff, Zulkfli (Institute of Graduate Studies, UiTM, 2018)
The research intends to trace the development of style, identify the factors that influence the style and finally to determine the identifiable style of Malay kukuran. Forty seven out of ninety seven kukuran were selected as sample for this research. The formal interpretation of visual composition is to depict it message and evaluate it in content. In the pre-iconographical interpretation, the researcher is analysing form and content in order to understand how kukuran design expresses or shapes the experiences, ideas and values of Malay craftsman's. Formal analysis, pre-iconographical and style are addresses the inquiry for meaning and represents some entity or concept. The research suggested that kukuran can be classified into four main groups; zoomorphic form, anthropomorphic form, modern form and utility form. In zoomorphic forms, it is subdivided into four small groups. The groups are Zoomorphic Simple Form, Zoomorphic Full Ornamental, Zoomorphic Stylized Ornament Form and Zoomorphic Semi Ornament Form. Prior to the Zoomorphic Full Ornamental, this group is dividing into three subgroup; Zoomorphic Stylized Animal Representations, Zoomorphic Abstract Animal Representations and Zoomorphic Stylized Mystical Creatures. The results of the study also suggested that the ornaments representation in kukuran has its own identity and value that reflect the form and soul of the Malay craftsmen. Each and every one of these ornaments representation has its own unique compositions and signifies to the Malay concept of beauty. This ornaments representation offers some understanding and insight into the Malay art form as well as in the spirit of Islam. The ornaments representational on the body of kukuran reflect the Malay world view on the concept of beauty, creativity and skill of the Malays craftsmen. Generally, ornaments representational use in kukuran can be classified into at least three different types which are floral ornaments, geometrical ornaments and combination both of them. The result of this research will surely be very useful to be used by those interested in studying traditional Malay material culture in general and kukuran art specifically. In the future, it will be great if other researcher continue research on the kukuran by incorporating two other level of Panofsky' iconological interpretation. In conclusion, the study of Malay material cultures gives an opportunity to infuse the traditional features into contemporary design and hopefully tend to establish national identity.